The etiquettes of agriculture in Islam / Zanirah Mustapha @Busu ...[et al.] - Mustafa @ Busu, Zanirah; Tasir, Siti Fatimah; Junoh,, Noraini; Zakaria, Nor Hidayah (Unit Penerbitan Universiti Teknologi MARA, Kelantan, 2017)
The purpose of this paper is to highlight Islamic etiquettes that need to be followed by everyone who is involved in the agricultural activities. The approach used in this writing is related to the etiquettes of agriculture according to the Al-Quran which need to be implemented in the agricultural activities. The agricultural ethics in Islam must be integrated and non-secular. It needs to be shariah compliance, abide by the rules of Allah SWT, not to be based on greed and any worldly rewards. The agricultural activities in Islam are oriented by the integration that cover the needs of each individual and the community. In Islam, the word adab (etiquettes) is known as akhlak as it is explained in the Al-Quran and Sunnah. The ethics of agriculture according to the perspectives of Islam can be categorized into three categories: the etiquettes towards Allah SWT, the etiquettes towards other humans and the etiquettes towards the universe. The outcome of this paper can deliver proper understandings of the etiquettes of agricultural activities which are parallel with the rules of Islam.